Antioxidant and Pro-Oxidant Effects of Polyphenolic Compounds and Structure-Activity Relationship Evidence - Yordi, Estela Guardado; Pérez, Enrique Molina; Matos, Maria João; Villares, Eugenio Uriarte (IntechOpen, 2012)
None